Halo-RPD: searching for RNA-binding protein targets in plants - A. O. Shamustakimova (Вавиловский журнал генетики и селекции)
Study of RNA-protein interactions and identification of RNA targets are among the key aspects of under-standing RNA biology. Currently, various methods are available to investigate these interactions with, RNA immunoprecipitation (RIP) being the most common. The search for RNA targets has largely been conducted using antibodies to an endogenous protein or to GFP-tag directly. Having to be dependent on the expression level of the target protein and having to spend time selecting highly specific antibodies make immunoprecipitation complicated. Expression of the GFP-fused protein can lead to cytotoxicity and, consequently, to improper recognition or degradation of the chimeric protein. Over the past few years, multifunctional tags have been developed. SNAP-tag and HaloTag allow the target protein to be studied from different perspectives. Labeling of the fusion protein with custom-made fluorescent dyes makes it possible to study protein expression and to localize it in the cell or the whole organism. A high-affinity substrate has been created to allow covalent binding by chimeric proteins, minimizing protein loss during protein isolation. In this paper, a HaloTag-based method, which we called Halo-RPD (HaloTag RNA PullDown), is presented. The proposed protocol uses plants with stable fusion protein expression and Magne® HaloTag® magnetic beads to capture RNA-protein complexes directly from the cytoplasmic lysate of transgenic Arabidopsis thaliana plants. The key stages described in the paper are as follows: (1) preparation of the magnetic beads; (2) tissue homogenization and collection of control samples; (3) precipitation and wash of RNA-protein complexes; (4) evaluation of protein binding efficiency; (5) RNA isolation; (6) analysis of the RNA obtained. Recommendations for better NGS assay designs are provided.